2014
DOI: 10.1016/j.jnnfm.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Slip flows of Newtonian and viscoelastic fluids in a 4:1 contraction

Abstract: a b s t r a c tThis work presents a numerical study of the 4:1 planar contraction flow of a viscoelastic fluid described by the simplified Phan-Thien-Tanner model under the influence of slip boundary conditions at the channel walls. The linear Navier slip law was considered with the dimensionless slip coefficient varying in the range ½0; 4500. The simulations were carried out for a small constant Reynolds number of 0.04 and Deborah numbers (De) varying between 0 and 5. Convergence could not be achieved for hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…Therefore, we can conclude that increase of the flow rate enhances the vortex length, which is the same as that given by Kim et al [22]. The vortex length increases with the increase of We, which is consistent with the results given by Ferrás et al's numerical simulation [24] and Lee and Ahn's experiment [25] for viscoelastic fluids in a 4:1 contraction. Actually the fact that the vortex length is larger for larger We is related to the larger extensional viscosity that increases the fluid flow resistance, and consequently, a larger portion of fluid recirculates, creating larger vortices.…”
Section: Effect Of Reynolds Number and Weissenberg Number On The Vortsupporting
confidence: 92%
“…Therefore, we can conclude that increase of the flow rate enhances the vortex length, which is the same as that given by Kim et al [22]. The vortex length increases with the increase of We, which is consistent with the results given by Ferrás et al's numerical simulation [24] and Lee and Ahn's experiment [25] for viscoelastic fluids in a 4:1 contraction. Actually the fact that the vortex length is larger for larger We is related to the larger extensional viscosity that increases the fluid flow resistance, and consequently, a larger portion of fluid recirculates, creating larger vortices.…”
Section: Effect Of Reynolds Number and Weissenberg Number On The Vortsupporting
confidence: 92%
“…Many works have adopted this model and showed that the size of the vortex increases with the ratio of the extensional to shear stresses [13,14,15]. Ferrás et al [16] used the PTT model along with slip boundary conditions. Increasing the slip enlarges the lip vortex until it absorbs the salient vortex.…”
Section: Introductionmentioning
confidence: 99%
“…MHD slip flow of viscoelastic fluid over the stretching surface has been investigated by Turkyilmazoglu [14]. Ferrás et al [15] analyzed the slip flow of Newtonian and viscoelastic fluids. e effect of slip and MHD on viscoelastic convection flow in a vertical channel has been discussed by Singh [16].…”
Section: Introductionmentioning
confidence: 99%